The Impact of Managerial Experience, Continuing Education, and Work-Life Balance on Innovation and Growth of Start-ups in Indonesia - Al Munip; Riani Prihatini Ishak; Marisi Butarbutar; Sisran Sisran; Muhammad Halfi Indra Syahputra (West Science Journal Economic and Entrepreneurship, 2024)
This study investigates the impact of managerial experience, continuing education, and work-life balance on the innovation and growth of startups in Indonesia. Using a quantitative approach, data were collected from 170 startup managers and analyzed using Structural Equation Modeling-Partial Least Squares (SEM-PLS). The results reveal that all three factors—managerial experience, continuing education, and work-life balance—positively and significantly influence the innovation and growth of startups. Continuing education emerged as the most influential factor, followed by work-life balance and managerial experience. These findings underscore the importance of ongoing learning, experienced leadership, and maintaining a healthy work-life balance in fostering startup success. The study provides valuable insights for entrepreneurs, managers, and policymakers seeking to enhance the innovation capacity and growth potential of startups in Indonesia.